2000
DOI: 10.1161/01.hyp.36.6.986
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the ACE D Allele and the GNB3 825T Allele in Myocardial Infarction

Abstract: Abstract-In polygenetic disorders, such as ischemic heart disease, the investigation of gene-gene interactions rather than determination of single gene effects is crucial to better understand the contribution of genetic factors. The 825T allele of the G-protein ␤ 3 -subunit gene (GNB3) associated with enhanced G-protein signaling is a candidate to interact with the angiotensin-converting enzyme (ACE) deletion/insertion (D/I) polymorphism to increase the risk for myocardial infarction (MI Key Words: myocardial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 41 publications
0
27
0
Order By: Relevance
“…38,43 This is because complex trait diseases such as EH are not regulated by single-gene effects but are often associated with multiple genetic and environmental factors. In the present study, we examined a significant interaction between the GNB3 and ACE genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38,43 This is because complex trait diseases such as EH are not regulated by single-gene effects but are often associated with multiple genetic and environmental factors. In the present study, we examined a significant interaction between the GNB3 and ACE genes.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we examined a significant interaction between the GNB3 and ACE genes. Naber et al 43 reported that a GNB3 C825T polymorphism interacts with the ACE I/D polymorphism in association with MI. They found a significantly increased OR for MI associated with the GNB3 825T genotype in individuals within the ACE DD genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…As the study was carried out with depressive patients without serious cardiac impairment at the time of the investigation, it was impossible to predict whether this combined action of the ID/DD Á TT genotype is increasing the risk for both disorders. Nevertheless that study reports for the first time that the same allelic combination of two genes that have been shown to increase the risk for myocardial infarction (Naber et al 2000) increase the vulnerability for depressive disorder. The C825T polymorphism was associated with seasonal affective disorder in another study sample (Willeit et al 2003).…”
Section: G-proteinsmentioning
confidence: 94%
“…NS ¼ nonsignificant. 295 increase the vulnerability for depressive disorder. 296 The reason why most genetic variability within pharmacodynamic elements did not turn out to be highly predictive of favorable antidepressant treatment response might be that most studies focused on short-time effects of antidepressants such as changes in the serotonin-or noradrenaline-pathways.…”
Section: Antidepressant Responsementioning
confidence: 99%